Common and Variation Peak Ratio Dual-Index Sequence Analysis of Vanillin-Sulfuric Acid Developing UV Fingerprint of Panax notoginseng - Zhong, Gui; Wang, Yuan-Zhong; Zhang, Ji; Zhao, Yan-Li; Zhang, Jin-Yu; Xiao, Yan-Bo (Asian Journal of Chemistry, 2014)
The vanillin-sulphuric acid developing-UV fingerprint of Panax notoginseng extracted by chloroform, ethanol and water was analyzed by common and variation peak ratio dual index sequence analysis. The results indicated that there was same effective quality evaluation for P. notoginseng extractions of chloroform, ethanol and water. The common peak ratios of the different seed sources and same producing areas of P. notoginseng ranged from 45 to 85 %, the variation peak ratios ranged from 9.38 to 61.90 %. There were relationships between results of experiment and information of samples. This method evaluated quality of P. notoginseng from different seed sources and same producing areas, which provided reference for quality evaluation of Chinese herbal medicine.